(3cJGH aj GdgjFIs - (3GdbQeGfj (B, (3GdBeOj, EHQGgje (B, (3cGf MjG (B1064 (3g`s ((3YHO GdMdje GdMdejs)
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb GdSeGhGJ hLejY GdYGde deG WGdYJ JGH GdgjFI Ydi GYJbGO Ggd GdSfI ddehdi GYeI CHj GdaVd LdGd GdOjf GdSjhWj hhLOJ eHGfj eHGMKgG eWGHbG deVehf GdGMGOjK hGdBKGQ s
(3BNQgG (B:s
(3bGd fYe Efj dCUObg HeG gh CHYO ef Pdc CUObg HNHQ GdSeGA aj ZOhI Ch QhMI adPdc Sej CHh HcQ GdUOjb QVj Gddg Yfg UOb QShd Gddg hUOb MHjH Gddg hfMf Ydi Pdc ef GdTGgOjf BNQ GdcdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1\53s
(3eYLe GdeDdajf (B1\53s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs